FANTASY CHARACTERISTICS IN THE WORKS OF URSULA LE GUIN AND KHUDAYBERDI TOKHTABOYEV - Hasanova Khurshidabanu Bakhtiyarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article reveals the cultural features of the fantasy genre in the works of Ursula Le Guin and Khudoyberdi Tokhtaboyev. Based on the results, literary sources are analyzed in terms of images. In particular, fantasy is characterized by such features as the transition from the personal transformation of the characters to their adventures, the change of the hero's journey based on the story, and the strengthening of the role.